2020
DOI: 10.1002/eem2.12079
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Preparation and Application of Nano‐Chitin Materials

Abstract: Chitin is a kind of natural macromolecule material which was first discovered in mushrooms and was widely found in the shells of crustaceans and arthropods, the cell walls of fungi (yeast and mold) and algae, and the mollusks. The original chitin in nature usually has an antiparallel molecular chain alignment forming nanofibers connected by inter-and intramolecular hydrogen bonds. These microfibers consist of nanofibers about 2-5 nm in diameter, and about 300 nm long, embedded by protein matrices. Due to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 150 publications
(193 reference statements)
0
43
0
Order By: Relevance
“…1 Biosorption studies using a natural polymer in its native or modified state are gaining more importance nowadays. A number of naturally occurring polymers that are abundantly available in nature and upon proper treatment have been reported as effective adsorbents are cellulose, 2-4 chitin 5,6 and chitosan, [7][8][9][10][11] alginates, 12,13 clays, 14 magnetic ferrites 15,16 and resins. 17,18 They are applied for the removal of various water pollutants such as heavy metals, 19,20 dyes in single 21,22 and binary systems, 23 pesticides, paints etc.…”
Section: Introductionmentioning
confidence: 99%
“…1 Biosorption studies using a natural polymer in its native or modified state are gaining more importance nowadays. A number of naturally occurring polymers that are abundantly available in nature and upon proper treatment have been reported as effective adsorbents are cellulose, 2-4 chitin 5,6 and chitosan, [7][8][9][10][11] alginates, 12,13 clays, 14 magnetic ferrites 15,16 and resins. 17,18 They are applied for the removal of various water pollutants such as heavy metals, 19,20 dyes in single 21,22 and binary systems, 23 pesticides, paints etc.…”
Section: Introductionmentioning
confidence: 99%
“…Chitin and its derivatives have been proved lack of toxicity and not expected to harm people, pets, and wildlife, generally recognized as safe (GRAS) status as a food additive by the U.S. Food and Drug Administration [ 57 – 59 ]. Nanochitin material has been widely used in biomedical development with good biocompatibility, biodegradability, and non-cytotoxicity [ 60 ]. Zhao et al [ 47 ] reported that nanochitin whiskers exhibited low toxicity at concentration lower than 50 µg/mL and had better cytocompatibility at 200 µg/mL concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The polymer can then be altered and rearranged to produce shapes and characteristics for the specific application. 15,68,69 The MW, DDA, cross-linking of the polymer chains and other molecular characteristics influence the mechanical properties of the product. 24,30…”
Section: Review Of Non-toxic Chitin Pre-treatment Methodsmentioning
confidence: 99%
“…The polymer can then be altered and rearranged to produce shapes and characteristics for the specific application. 15,68,69 The MW, DDA, cross-linking of the polymer chains and other molecular characteristics influence the mechanical properties of the product. 24,30 Nanomaterials can be produced by a "top-down" or "bottom-up" approach: top-down refers to the production of nanofibers by fibrillation (separation of thick fibres into many thin fibres), while the bottom-up approach refers to the reassembly of nanofibers from a dissolved state, for example by self-assembly or electro-spinning.…”
Section: Review Of Non-toxic Chitin Pretreatment Methodsmentioning
confidence: 99%
See 1 more Smart Citation